Risikowahrnehmung und Verbrauchervertrauen nach einem Lebensmittelskandal: Eine experimentelle Studie; Risk perception and consumer trust after a food scare: An experimental analysis - Andreas Boc̈ker; Silke Albrecht (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– An expected utility model with Baysean information processing that explains the extent of consumer reaction to a food scare by the degree of supplier differentiation with respect to reliability is put to an experimental test. The empirical results offer no support for the theoretical prediction that post food scare consumer trust in a particular supplier decreases with an increasing degree of differentiation. While gender and personal experience with a food poisoning contribute significantly to the explanation of the individual level of consumer trust after the - hypothetical - food safety incident, perceived characteristics of the specific risk factor listeriosis chosen for this study had by far the biggest impact.
Keywords: 330; Lebensmittelsicherheit; Lebensmittelsicherheit; Konsumentenverhalten; Vertrauen; Erwartungsnutzen; Experiment